The effect of exercises utilizing a device design in strengthening the endurance of the throwing hand's particular strength and the precision of targeting the index of stability for young handball players (Journal of Humanities and Social Sciences Research, 2023)
Shooting is one of the fundamental skills that coaches must emphasize in its different forms, depending on the defensive position that dictates the usage of any form or style of shooting, which has gotten highly developed for what most clubs and teams employ to reach their goals through improved defence. So long as the firing procedure necessitates a specific force (explosive ability, a force differentiated by speed, carrying power) in order to accommodate this advancement in defence, As well as it creates weapons that aid in the resolution of attacking positions, as well as the presence of a goalie. As a result, it has become one of the coach's primary roles to focus on completing the shooting procedure with maximum strength, speed, and accuracy. In order to render the situation tough for the defender and goalie, extensive training is required so that the task is executed with the best outcomes possible. As a consequence, the researcher considers building two training devices based on scientific foundations and is meant to achieve the objective of developing the corrective process in its many forms under examination.